B03 An investigation into the effects of cryo-compression versus TECAR therapy on symptoms of exercise-induced muscle damage - Jones, Kai; Skinner, Brendon; Cuttell, Saul (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Exercise-induced muscle damage (EIMD) results from unaccustomed exercise in which the observed effects are reported to last up to 96h (Peake et al., 2017, J Appl Physiol, 122). The use of both cryotherapy and thermal interventions have been explored for reducing the symptoms of EIMD however their effectiveness has been debated with conflicting views on the efficacy of both interventions. This study aimed to directly contrast the effectiveness of cryotherapy and thermal applications on symptoms of EIMD. Ethical approval was granted by the University of Northampton Sport and Exercise Ethics Committee. Twenty-eight (N=28, 10 female) moderately active participants (120-180 min a week; age 19.9 ±1.38 years, stature 174.8 ± 8.9 cm, mass 73.8 ± 15.5 kg) participated in an independent-subject design trial. At 0 h participants performed baseline tests (VAS, MVIC, CMJ and MTC) and then a fatigue protocol (20 × 5 box drop-jumps at 60 cm). Measures of EIMD were assessed over 96 h before random allocation to 15-min of TECAR (0 h= 10%, 24 h= 20%, 48 h= 30%, 72 h= 40%), Game-Ready (1˚C with an average pressure of 50 mmhg over 180 s) or control groups (seated rest). A two-way mixed model ANOVA with Bonferroni post-hoc pairwise comparison analyses were conducted. A Friedmans ANOVA was conducted for combined VAS data with a post-hoc Wilcoxon test. Within-group analysis revealed significant differences in MVIC (P = 0.001, n2 = 0.573) with interaction effect by condition (P = 0.021, n2 = 0.161). Pairwise comparisons revealed effects following TECAR at 0-24 h, P=0.009 (−10.2%), 0-48 h, P=0.033 (−9.5%), Game-Ready at 0-24 h, P = 0.001 (−15.0%), 0-48 h, P = 0.001 (−16.5%), 0-72 h, P = 0.001 (−12.3%) and control at 0-24 h, P = 0.001 (−12.8%), 0-48 h, P=0.008 (-10.8%). No significant differences were found at baseline between VAS scores (P=0.154), but significant differences were found at all other time points for all conditions (P < 0.05). TECAR resulted in the least performance decrements but experienced the greatest pain, compared to the Game-Ready, which resulted in the greatest performance loss but experienced the least pain. Neither TECAR nor Game-Ready appear advantageous over each other in attenuating symptoms of EIMD.